Versatile radiofrequency sensor - Borges, R; Bari, M; Coey, J; Gregg, J; Thornton, M; Allen, W (2001)
A miniature, monolithic radiofrequency sensor operating with MESFET circuitry in the GHz range is able to detect a wide variety of magnetic, metallic and dielectric materials via the losses induced in the sensitive volume around a coil. Application of the sensor to detect plastic and metal gearwheels and falling liquid drops is illustrated; the signal-to-noise ratio falls off as the inverse distance from the coil to the liquid drop. (C) 2001 Elsevier Science B.V. All rights reserved.